2013
DOI: 10.2527/jas.2013-6490
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for calving and conformation traits in Charolais × Montbéliard and Charolais × Holstein crossbred calves1

Abstract: Charolais sires can be mated to Montbéliard or Holstein dairy cows to produce crossbred calves sold for meat production. Heritabilities and correlations between traits can differ when they are calculated within Charolais × Montbéliard or within Charolais × Holstein population. Moreover, the genetic correlation between the same trait measured on Charolais × Montbéliard and on Charolais × Holstein crossbred calves is not necessarily unity. The first objective of this study was to estimate heritability and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(29 reference statements)
2
10
0
Order By: Relevance
“…The correlation among the random regression coefficients used to adjust the sires BV did not differ from zero (Table 7), as found by Vallée et al (2013) and Ribeiro et al (2017). Those authors demonstrated that the sire BV is related to the breed composition of their progeny and the BV obtained by purebred progeny records differs from that of crossbred progeny.…”
Section: Field Datamentioning
confidence: 69%
See 2 more Smart Citations
“…The correlation among the random regression coefficients used to adjust the sires BV did not differ from zero (Table 7), as found by Vallée et al (2013) and Ribeiro et al (2017). Those authors demonstrated that the sire BV is related to the breed composition of their progeny and the BV obtained by purebred progeny records differs from that of crossbred progeny.…”
Section: Field Datamentioning
confidence: 69%
“…Therefore, the development and implementation of genetic evaluations that account for genotypic means, genetic covariances among relatives (Lo et al, 1993), and the existence of specific genetic variances for each different breed group (Lukaszewicz et al, 2015) can contribute to the genetic improvement of multiple-breed populations. In addition, the identification of the interaction between progeny breed group and the breeding value (BV) of sires (Vallée et al, 2013;Lukaszewicz et al, 2015) can help in designing mating strategies and improve genetic gain over generations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other classifier scored 839 Montbéliard × Charolais calves and 206 Holstein × Charolais calves. More details on traits and data collection can be found in Vallée et al (2013).…”
Section: Datamentioning
confidence: 99%
“…Variance components used in BLUP and GBLUP were fixed at values estimated from a larger data set described in Vallée et al (2013) in which calves from both crossbred populations were included and traits were assumed genetically similar between populations. Genetic variance and residual variance were 0.121 and 0.407 for bone thinness, 0.198 and 0.391 for height, and 0.661 and 1.025 for muscular development, respectively.…”
Section: Estimation Of Breeding Valuesmentioning
confidence: 99%